Desarrollo de un libro interactivo basado en la obra las artesanías de la provincia de Loja del autor Dr. Gabriel Gonzalo Gómez Gómez para dispositivos móviles con sistema operativo android versión 4.2, como fuente de consulta para los docentes en el área de lengua y literatura de la unidad educativa La Inmaculada Concepción de Loja - Moreira Celi, José Pablo (2015)
The lack of knowledge of the teachers and principals about the benefits of using mobile devices and their applications have not been exploited so that can facilitate, support and enhance the teaching-learning process; for that reason in the city of Loja they have chosen to ban the use of these devices considered distracting or entertaining elements. Educational establishments such as the Immaculate Education Unit, an institution where the study was conducted, it was evident that such difficulties do not use mobile technology in the classroom, where let it acquire knowledge in an innovative and attractive way when to learn or generate significant learning. Therefore it is planned to elaborate an interactive mobile book being used methodology Iconix for development, allowing comply with each of the objectives and especially to socialize the application to teachers of the institution to disclose the usefulness and benefits of mobile technology in education. The tools used to develop and evaluate interactive book of the "Crafts of the Province of Loja" were the most favorable. Also one of the techniques used was the survey which sufficient for completion of the application data is obtained; the same that was widely accepted by teachers and administrators, by the way people interact and navigate within it. Based on the socialization and the results presented in this research work it is concluded that the incorporation of this type of resources that handle interactivity in the teaching-learning process, supports and strengthens meaningful learning in students.